2021
DOI: 10.3390/ma14174884
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Effect of Arc and Ultrasonic Energy on MIG Arc Ultrasonic Welding

Abstract: Ultrasonic energy is introduced into the Metal Inert Gas (MIG) welding arc and weld pool by superposition of an ultrasonic frequency current. In this study, the arc shape, arc energy, and ultrasonic energy that responded to ultrasonic excitation voltage and frequency is investigated. The comprehensive influence of arc and ultrasonic energy on weld formation, microstructure, and mechanical properties is further studied. The arc and ultrasonic energy are analyzed by using a high-speed camera and microphone, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…During the arc welding process, the grain structure of the weld metal becomes coarse and thus causes deterioration of the welding mechanical properties [100]. A number of studies [101][102][103][104] have found that stirring the weld pool is beneficial for enhancing the properties of welded joints. Due to the weld pool stirring effect, dendrite fragmentation and grain detachment occur.…”
Section: Weld Pool Stirringmentioning
confidence: 99%
“…During the arc welding process, the grain structure of the weld metal becomes coarse and thus causes deterioration of the welding mechanical properties [100]. A number of studies [101][102][103][104] have found that stirring the weld pool is beneficial for enhancing the properties of welded joints. Due to the weld pool stirring effect, dendrite fragmentation and grain detachment occur.…”
Section: Weld Pool Stirringmentioning
confidence: 99%